Implementation of the INTERGROWTH‐21st Project in India. (17th May 2013) - Purwar, M; Kunnawar, N; Deshmukh, S; Singh, A; Mulik, I; Taori, V; Tayade, K; Mahorkar, C; Somani, A; Saboo, K; Choudhary, A; Shembekar, C; et al.
Abstract : The South Asian site in the INTERGROWTH‐21 st Project was the city of Nagpur, in Maharashtra State, India, with approximately 4500 births per year among the target population with middle to high socio‐economic status. These deliveries are mainly concentrated in 20 small private hospitals, most of which are in the city centre. The sample for the Newborn Cross‐Sectional Study (NCSS) was drawn from ten of these hospitals, covering 76% of the target low‐risk pregnant population. The Fetal Growth Longitudinal Study (FGLS) sample was recruited from the largest of these institutions, Ketkar Hospital, as well as several ancillary antenatal care clinics. Special activities to encourage participation and raise awareness of the study at this site included translating patient information leaflets into local languages and securing local media interest. Among the unique challenges of the Indian site was the coordination of the large number of hospitals involved in NCSS, a task that required careful planning and organisation by the field teams.